THE EFFORTS OF ERADICATION OF CORRUPTION THROUGH INSTRUMENTS OF MONEY LAUDERING LAW AND RETURN ACTORS’ ASSETS - Yasmirah Mandasari Saragih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In the period up to 2015 human rights crimes have evolved into the deprivation of economic rights and social property of the people through political corruption that spreads endemically. Despite the human rights was guaranteed in the 1945 amendments and various other legal devices yet our country has ratified many international conventions on human rights, but human rights violations in a variety of shades and variations remains widespread. This proves that guarantees of protection of human rights in writing still needs to be guarded by the implementation of all national components, especially public institutions such as the media, NGOs, organizations and universities. Refund of state financial in consequence of corruption is an effort to reform and build legal institutions to prevent and combat corruption in international, regional and national levels. Asset recovery efforts must be made by the Indonesian government, because: regarding to the data losses to the state, Indonesia is considered as the country victims of corruption; The corrupted funds are funds that should be devoted in order to improve the prosperity and welfare; Funds taken by the corruptors must be returned as one of the sources of funding in the creation of public welfare; an effort of refund as a preventative measure to potential offenders. Keywords: Corruption, Money Laundering, Asset Refund.